Clinical and neuropsychological outcome of pediatric non‐midline central nervous system germinoma treated with chemotherapy and reduced dose/volume irradiation: The Children's Hospital Los Angeles experience. Issue 12 (10th September 2019) - Yeo, Kee Kiat; Kayser, Kimberly; Margol, Ashley S.; Wong, Kenneth K.; Robison, Nathan; Finlay, Jonathan; Dhall, Girish
Abstract: Background: Germ cell tumors (GCT) arising from non‐midline structures (basal ganglia, thalamus, and posterior fossa) are rare. Although patients with midline (pineal and suprasellar) germinoma have excellent survival with chemotherapy and whole ventricular irradiation (WVI), germinoma in non‐midline locations have traditionally been treated with craniospinal irradiation (CSI) or whole brain irradiation (WBI) to achieve similar outcomes. However, CSI and WBI are associated with significant long‐term neuropsychological sequelae. Methods: We describe the clinical and neuropsychological outcomes of patients with non‐midline germinoma treated at the Children's Hospital Los Angeles between 1990 and 2015. Results: Nine patients had basal ganglia/thalamic germinoma and one patient had a cerebellar primary. Eight patients received chemotherapy followed by reduced dose/volume irradiation, whereas two patients received chemotherapy alone as upfront therapy. One patient in the chemotherapy alone group relapsed after 4.3 years and was salvaged with CSI plus boost. The overall survival for the entire cohort was 100% at a median follow‐up of 8.5 years. Neuropsychological data were available for six patients at a median of five months (baseline) and 4.2 years (follow‐up) post‐diagnosis. At four‐year follow‐up, data available revealed intact overall cognitive ability, verbal memory, and executive functioning, but persistent deficits in fine motor function. Comparison of baseline to follow‐up suggests a downward trend in working memory, planning/problem‐solving, verbal memory, and visuospatial integration. Conclusion: Chemotherapy followed by reduced dose/volume of irradiation is an effective strategy resulting in long‐term survival in patients with non‐midline germinoma. Neuropsychological data suggest relatively minimal morbidity over time.